PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILTY SEBAGAI VARIABEL MODERATING - Munawaroh, Aisyatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the disclosure influence of corporate social responsibility inmoderating the relation between the profitability and the company value. The population is manufacturingcompanies which are listed in IDX in 2009 â 2012, the sample collection technique is carried out by usingpurposive sampling method and based on the determined criteria so the samples are 11 manufacturingcompanies which have continuously published their annual report and have implemented the practice ofcorporate social responsibility during the period of 2009-2012. The research hypothesis is performed by usingmultiple linear regressions analysis technique with the assistance of SPSS application. The result of researchshows that Return On Assets (ROA) has significant negative influence to the companyâs value, Return OnEquity (ROE) and Net Profit Margin (NPM) have significant positive influence to the companyâs value,Corporate Social Responsibility variable is unable to influence to the relation between Return On Assets (ROA)and Net Profit Margin (NPM) to the companyâs value while the Corporate Social Responsibility is able toinfluence the relations between Return On Equity (ROE) to the companyâs value.Keywords: ROA, ROE, NPM, Corporate Social Responsibility, and Company Value.